تدبير سرطانة القولون الأعور دراسة في مشفى الأسد الجامعي بدمشق - الشلبي عبد الغني (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث لدراسة تواتر سرطانة القولون الأعور وطرق كشفها وتدبيرها في مشفى الأسد الجامعي بدمشق سواء بالجراحة التقليدية أم التنظيرية، وقد أجري البحث بالطريقة المستقبلية والراجعة من خلال المتابعة لـ/72/ مريض مصاب بسرطانة القولون الأعور خلال فترة خمس سنوات ما بين عامي كانون الثاني /2002 وكانون الأول/2007. ولقد بينت الدراسة أن استئصال الكولون الأيمن الواسع (extended right hemi- colectomy) مع تجريف العقد المرافق سواء بالجراحة التقليدية أم التنظيرية يمثل العلاج الأمثل لهذا المرض شديد الخطورة إن لم يعالج باكراً، وتظهر الدراسة أنه كلما تم التشخيص والعلاج بصورة مبكرة كلما كانت النتائج والإنذار أفضل. وقد أجريت المفاغرة الدقاقية الكولونية إما يدوياً أو باستعمال الستابلر وكانت النتائج متقاربة مع نسبة اختلاطات إجمالية (29.1%). ونخلص إلى القول: إن التشخيص والعلاج الباكرين يعطي أفضل النتائج مما لو كان التشخيص متأخراً والحالة متقدمة. The goal of this research is to study the frequency of cecum cancer and consider ways of diagnosing and managing it at Al-Assad University Hospital in Damascus, either in open or laparoscopic surgery. The research is done in antegrade and retrograde approach by constant monitoring of 72 patients. This research is carried out on 72 patients having cecum cancer during a 5-year period of time between January 2002 and November 2007. This study shows that the extended Right Hemicolectmy with lymphaden-ectomy either in open or laparoscopic surgery is the ideal treatment for this extremely dangerous disease, especially if it is not treated early. The study concludes that the sooner the diagnosis and treatment are done, the better the results and prognosis will be. Ileo-Transverse colon–anastomosis is performed manually or by using staplers, and the results are almost the same with a complication rate of 29.1%. In conclusion, the sooner the diagnosis and treatment, the better.